Culturable Bacterial Endophytes Associated With Shrubs Growing Along the Draw-Down Zone of Lake Bogoria, Kenya: Assessment of Antifungal Potential Against Fusarium solani and Induction of Bean Root Rot Protection - Mutungi, Priscillar Mumo; Wekesa, Vitalis Wafula; Onguso, Justus; Kanga, Erustus; Baleba, Steve B. S.; Boga, Hamadi Iddi (Frontiers in Plant Science, 2022)
Vascular shrubs growing along the draw-down zones of saline lakes must develop adaptive mechanisms to cope with high salinity, erratic environmental conditions and other biotic and abiotic stresses. Microbial endophytes from plants growing in these unique environments harbor diverse metabolic and genetic profiles that play an important role in plant growth, health and survival under stressful conditions. A variety of bacterial endophytes have been isolated from salt tolerant plants but their potential applications in agriculture have not been fully explored. To further address this gap, the present study sought to isolate culturable bacterial endophytes from shrubs growing along the draw-down zone of Lake Bogoria, a saline alkaline lake, examine their functional characteristics and potential in biocontrol of the bean root rot pathogen, Fusarium solani. We collected shrubs growing within 5 meters from the shoreline of Lake Bogoria and isolated 69 bacterial endophytes. The endophytic bacteria were affiliated to 3 different phyla (Firmicutes, proteobacteria and Actinobacteria) with a bias in the genera Bacillus and showed no tissue or plant specificity. All selected isolates were positive for catalase enzyme; grew in 1.5M NaCl; three isolates (B23, B19 and B53) produced Indole Acetic Acid (IAA) and only one isolate, B23 did not solubilize phosphate on Pikovskaya agar. Isolates B19 and B53 exhibited more than 50% mycelial inhibition in dual culture assay and completely inhibited the germination of Fusarium solani spores in co-culture assays while two isolates, B07 and B39 had delayed fungal spore germination after an overnight incubation. All isolates were able to establish endophytic association in the roots, stems and leaves of been seedlings in both seed soaking and drenching methods. Colonization of bean seedlings by the bacterial endophyte B19 and B53 resulted in biocontrol of Fusarium solani in planta, reduced disease severity and incidence and significantly increased both root and shoot biomass in comparison with the control. Taxonomic identification using 16S rRNA revealed the two isolates belong to Enterobacter hormaechei subsp. xiangfangensis and Bacillus megaterium. Our results demonstrate the potential use of these two isolates in biocontrol of the bean root rot pathogen, Fusarium solani and plant growth promotion.